The impact of general self-efficacy and the severity of malocclusion on acceptance of removable orthodontic appliances in 10- to 12-year-old patients - Navid Naseri; Tahereh Baherimoghadam; Niloofar Bassagh; Shahram Hamedani; Elmira Bassagh; Zahra Hashemi (BMC, 2020)
Abstract Background The patients' acceptance of a treatment plan and their subsequent cooperation play a crucial role in achieving the best results in orthodontic treatments. Evidences show some personality traits such as general self-efficacy (GSE) and some dental traits such as severity of malocclusion are correlated with motivation of orthodontic treatment. These factors may predict the patients' compliance and acceptance in using removable orthodontic appliances. This cross sectional study was conducted to assess the correlation of GSE and the severity of malocclusion with patients' acceptance in using removable orthodontic appliances. Methods This study recruited 50 patients aged 10-12 years who required removable orthodontic appliances. The severity of malocclusion was determined using the index of orthodontic treatment need (IOTN) before the onset of treatment and GSE of participants were assessed using GSE scale self-report. The acceptance questionnaire was proposed to the patients on first (T1), third (T2), and sixth (T3) month after the delivery of the appliance. Results The GSE score had a statistically significant correlation with the total score of the acceptance questionnaire, subscale score of satisfaction with the appliance during eating and oral hygiene practice, duration of usage of the appliance, and interest in using it (P < 0.05). The IOTN had no significant correlation with the acceptance questionnaire. Conclusions Our findings substantiate the role of the GSES, concurrently declining the role of the IOTN in prediction of 10-12-year-old children's acceptance and cooperation in treatment of malocclusion with removable appliances.